ANALYSIS OF FACTORS AFFECTING TRADITIONAL ARAK PRODUCTION IN KUBU DISTRICT, KARANGASEM REGENCY - I Nyoman Rama Danu Artha; Ni Putu Martini Dewi (Adisam Publisher, 2026)
This study aims to analyze the factors that affect traditional arak production in Kubu District, Karangasem Regency. The variables examined in this study include capital, raw materials, labor, and work experience as production factors that are assumed to have the effect on the level of traditional arak production. This study is important because Kubu District is one of the largest centers of arak producers in Karangasem Regency, yet it still faces diverse production dynamics among business actors. By understanding the variables that play a role in increasing production, this study is expected to serve as a basis for strengthening the local economy based on the community’s traditional potential and local wisdom. This study employs a quantitative approach using multiple linear regression analysis to examine the effect of capital, raw materials, labor, and work experience, both simultaneously and partially, on the level of traditional arak production. The research sample consists of 83 arak producers selected using the proportionate stratified random sampling method. The results show that capital, raw materials, labor, and work experience have a significant effect on traditional arak production, both simultaneously and partially. These findings confirm that increasing production capacity can be optimized through the provision of stable raw materials, capital support, labor absorption, and skill improvement through experience.